SISTEM INFORMASI AKUNTANSI LABA - Hertati, Lesi; Puspitawati, Lilis (Jurnal Riset Akuntansi, 2025)
The purpose of this study is to examine the effect of accounting information system literacy on sales volume, operating costs and product excellence. The shape, packaging and design as well as the excellence of the goods remain prime and the price remains the same, because the quality of the goods remains number one in the eyes of buyers. This study used a sample of 125 food and beverage sub-sector manufacturing companies listed on the IDX from 2020 to 2024. The test tool used was regression analysis which measures the effect of independent variables on dependent variables and uses independent variables to predict dependent variables. The results of the study confirmed that sales volume and operating costs affect accounting information system literacy. Keywords: Sales Volume, Overational Costs, Accounting Information Systems, Profit, Competitive Advantage.